Mosaic Evolution of Grasping and Genital Traits in Two Sympatric Scorpion Species with Reproductive Interference - Oviedo-Diego, Mariela A.; Mattoni, Camilo I.; Bollatti, Fedra A.; Soto, Eduardo M.; Peretti, Alfredo V. (Evolutionary biology, 2024)
Components of the same structure or characters of the same individual might respond differently to natural and sexual selective pressures, showing complex morphological patterns. Besides, studying interactions between species plays a crucial role in understanding the diversification of sex-linked phenotypes. Specifically, when two closely related species coexist and exhibit interspecific sexual interactions (reproductive interference—IR), key traits for mating can diverge in sympatric areas to prevent interbreeding and ensure reproductive isolation (reproductive character displacement—RCD). RCD is primarily driven by natural selection, although sexual selection pressures can alter the pattern of phenotypic variation. Additionally, to gain a comprehensive understanding of the patterns of morphological diversification, it is essential to consider changes related to phenotypic plasticity across environmental gradients. To date, there are no studies evaluating this topic in scorpions, and two sympatric species ( Urophonius brachycentrus and U. achalensis ) with RI, provide an ideal model for evaluating phenotypic variation across environmental gradients and the presence of RCD. In this study, we compared intra-specific variation, as well as the size and shape of multiple characters involved in courtship and sperm transfer, between individuals from sympatric and allopatric populations using geometric morphometrics. Our findings revealed an increase in the size of various characters at lower temperatures (higher altitudes) for U. brachycentrus , making them more similar to heterospecifics in sympatric areas, resulting in a pattern of morphological convergence between these species. Increased similarity between species combined with a scramble competition mating system could intensify sexual selection pressures on particular characters. Furthermore, we identified asymmetric RCD in the shape of several sexual characters crucial for mating success (grasping structures) and sperm transfer (genital characters), which could potentially be significant for mechanical isolation during interspecific interactions. Our results highlight significant morphological variability in the size and shape of somatic and genital characters in two scorpion species. This variability may reflect different evolutionary responses, driven in part by natural selection pressures associated with geographic and environmental variations and species recognition mechanisms, and in part by sexual selection pressures at both the intra- and interspecific levels. This comprehensive study reveals the complexity of evolving multifunctional traits in an understudied model and offers valuable insights into traits subject to multiple selective pressures in animal systems experiencing RI.